Law and revolution : legitimacy and constitutionalism after the Arab Spring - Sultany, Nimer (Oxford : Oxford University Press, 2018)
This title provides an assessment of constitution-making, law, and revolution before and after the Arab Spring. Competing conceptualist approaches to the role of shari'a law in Arab constitutions are explored with a view to evaluating the consequences of different constitutional arrangements, and suggesting possibilities for reform.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 7, 2017).
Keywords: Arab Spring, 2010-; Arab countries -- Politics and government -- 21st century; Constitutional history -- Arab countries; Islamic law; Politics and Government; Politics & government